Morpho-Biological study of the parasitoid Compsilura concinnata (Meigen, 1824) (Diptera: Tachinidae)on Pieris rapae Larvae (Lepidoptera: Pieridae) - رمضان علي; أصلان لؤي; الخطيب ناديا; أحمد إسراء (Latakia University Journal -Biological Sciences Series, 2021)
The study was carried out at the laboratory of Entomology, Faculty of Agriculture, Tishreen University, after the larvae and pupae of Pieris rapae were collected from fields planted with cabbage from different regions in Lattakia from September to December. The percentage parasitism of C.concinnata parasitoid on host larvae was 47.61%, 41.77% during 2019 and 2020 respectively. The results of the study showed that :Female and Male life period/days with feeding on 50% solution of honey and water in the two different parasitism (solitary and superparasitism) were 6.74 ±0.24, 5.68 ± 0.24 days for female, 5.76 ± 0.94, 4.52 ± 1.36 days for male, while larvae and pupae were 13.32 ± 0.89, 10.2 ± 4.58 days and 13.04 ± 2.10, 10.2 ± 2.22 days respectively.